2015
DOI: 10.1589/jpts.27.3147
|View full text |Cite
|
Sign up to set email alerts
|

Color temperature’s impact on task performance and brainwaves of school-age children

Abstract: [Purpose] This study investigated color temperature’s impact on task performance. It presents a scientific analysis of brainwave and task performance time changes, and the results of a self-report type survey. [Subjects] Twenty-four elementary school fifth-grade boys and girls with no visual problems participated in the experiment. [Methods] Physiological reaction times of task performance were measured in a laboratory that could fix and maintain color temperature. Brainwave changes and the task performance ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The appearance of lighting is the CCT of light. In another experiment, the former hypothesis is further endorsed to test the influence of lighting colours on human task performance but instead focuses only on mesopic vision [44,45]. The findings were consistent with the fact that the response time of humans to a concerted physical activity in a room differs at various CCT extremes.…”
Section: Humans Reaction To Color Correlated Temperature (Cct) Parametersupporting
confidence: 54%
See 1 more Smart Citation
“…The appearance of lighting is the CCT of light. In another experiment, the former hypothesis is further endorsed to test the influence of lighting colours on human task performance but instead focuses only on mesopic vision [44,45]. The findings were consistent with the fact that the response time of humans to a concerted physical activity in a room differs at various CCT extremes.…”
Section: Humans Reaction To Color Correlated Temperature (Cct) Parametersupporting
confidence: 54%
“…Although the biological shift to lighting parameters is prevalent, the paper provided concrete evidence that students were in a calming mood at lower CCTs. Students were alert at the other higher extreme of CCT [44].…”
Section: Humans Reaction To Color Correlated Temperature (Cct) Parametermentioning
confidence: 99%
“…This finding is consistent with that found by Park. 18 They investigated the impact of colour temperature on task performance and found that alpha waves were more activated by a lower colour temperature.…”
Section: Resultsmentioning
confidence: 99%
“…17 Park et al. 18 tested the impact of colour temperature on school-age children by changing the static light on a fixed schedule. Their results indicated that the physiological reaction, concentration-related brainwaves, was elicited more strongly under light with a relatively high CCT.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have shown inconsistent results. For instance, some empirical results [52,53] did not support the suggestion that higher CCT benefits students in terms of focused attention and performance [11,18]. In the experiment of [11], contradictory results were found between participants from grade four and grade six.…”
Section: Customization Of Lighting Modesmentioning
confidence: 88%